Acute citalopram administration produces correlated increases in plasma and salivary cortisol. - Bhagwagar, Z; Hafizi, S; Cowen, P (2002)
RATIONALE: Intravenous administration of the selective serotonin (5-HT) re-uptake inhibitor, citalopram, increases plasma cortisol. This would be expected to produce a parallel increase in salivary cortisol concentration. OBJECTIVE: To find out whether IV citalopram produces correlated increases in plasma and salivary cortisol levels. METHODS: Twelve healthy volunteers were tested on two occasions receiving either citalopram (10 mg IV) or saline in a double-blind, randomised, cross-over design. Plasma and salivary cortisol levels were measured before and for 150 min after each infusion. RESULTS: Relative to placebo, citalopram significantly increased cortisol levels in both plasma and saliva. The size of the increases in plasma and saliva cortisol correlated significantly with each other. CONCLUSIONS: Monitoring changes in salivary cortisol might be a valid and acceptable means of measuring 5-HT-mediated cortisol release.